Microfiber Nonwovens as Potential Membranes. Issue 4 (2nd October 2019) - Kiyak, Yasar; Mazé, Benoît; Pourdeyhimi, Behnam
Abstract : This article provides an overview of the membrane bioreactor technology where nonwovens can be applied as an alternative medium for separation. The main objective is to identify the nonwoven characteristics leading to higher removal efficiency, higher flux, and lower fouling behavior. The general limitations associated with common nonwoven separation media are related to the large pore and wide pore size distributions. Consequently, due to their large pore network, nonwovens often behave as a depth filter structure. Common nonwovens having large fibers cannot replace microfiltration membranes yet. Further refinements of these structures are necessary for developing a suitable replacement.